Chemical analysis and flavor properties of blended orange, carrot, apple and Chinese jujube juice fermented by selenium-enriched probiotics. (15th August 2019) - Xu, Xinxing; Bao, Yejun; Wu, Bingbing; Lao, Fei; Hu, Xiaosong; Wu, Jihong
Highlights: Selenium-enriched probiotics and fermented Selenium-enriched FVJ were prepared. pH, viable counts, contents of free amino acids and organic acids were ascertained. Flavor substances and aroma-active components were identified. Correlation analysis of aroma-active components and chemical factors was investigated. Abstract: Preparation of selenium-enriched probiotics and Se-enrichment of probiotic-fermented blended juices were performed and optimized using orthogonal test. Se content had a significant 13.0-fold increase by the addition of 1% Se-enriched Streptococcus thermophilus starters in juice fermentation. Chemical properties of fermented blended juices were determined. Reducing sugar content decreased significantly after fermentation, and the same downtrend was observed for free amino acids and organic acids, with lactic acid being an exception. Meanwhile, dynamic variation analysis of flavor components during the fermentation, and characteristic aroma-active compounds before and after fermentation were demonstrated by GC–MS and GC–O. Eleven aroma-active substances were identified from juices without fermentation, while 7 characteristic compounds were detected in fermented juices. Furthermore, potential correlations between chemical and flavor characteristics were explored based on multivariate statistical analysis. These results indicate that a potential Se-enriched fermented beverage was established, and the fermentation process led to differences in the chemical substrates and impact odorants.